Outcome of small cell lung cancer (SCLC) patients with brain metastases in a routine clinical setting - Lekič, Mirko (Radiology and oncology (Ljubljana), 2012)
Background. Small cell lung cancer (SCLC) represents approximately 13 tomediansurvival of SCLC patients treated by specific therapy (chemotherapy andžor radiotherapy) with regard to the 18%months in patients treated with standard chemotherapy and radiotherapy. Inpresence or absence of brain metastases at the time of diagnosis. Patients and methods. All SCLC patients have been treated in a routine clinical practice and followed up at theUniversity Clinic Golnik in Slovenia. In the retrospective study the medical files from 2002 to 2007 were review. All patients with cytological or histological confirmed disease and eligible for specific oncological treatment were included in the study. They have been treated according to the guidelines valid at the time. Chemotherapy and regular followed-up were carried out at the University Clinic Golnik and radiotherapy at the Institute of Oncology Ljubljana. Results. We found 251 patients eligible for the study. The median age of them was 65 years, majoritywere male (67%), smokers or ex-smokers (98%), with performance status 0 to 1 (83%). At the time of diagnosis no metastases were found in 64 patients(25.5%) and metastases outside the brain were presented in 153 (61.0%). Brain metastases, confirmedby a CT scan, were present in 34 patients (13.5%), most of them had also metastases at other localisations. (Abstract truncated at 2000 characters)
Keywords: drobnocelični rak; metastaze; možgani; pljuča; rak (medicina)